Case Report: A Case Report and Literature Review of 3p Deletion Syndrome - Fu, Junxian; Wang, Ting; Fu, Zhuo; Li, Tianxia; Zhang, Xiaomeng; Zhao, Jingjing; Yang, Guanglu (Frontiers in Pediatrics, 2021)
Objective: The aim of the present study is to explore the clinical and genetic characteristics of the 3p deletion syndrome to improve clinicians’ understanding of the disease. Methods: The clinical manifestations, process of diagnosis and treatment, and genetic characteristics of an individual case of 3p deletion syndrome were analyzed. CNKI, Wanfang Data, and the Biomedical Literature Database (PubMed) were searched. The search time limit was from the creation of the database to June 2020 with “3p deletion syndrome,” “3p deletion syndrome,” and “BRPF1” as keywords. Related data were reviewed. Results: The proband was a male child with general developmental retardation, special facial features (bilateral ptosis, left auricle deformity, long philtrum, high arched palatal, micrognathia) and congenital heart disease. The child was the parents’ first pregnancy and first child. Gene microarray analysis showed a 10.095mb deletion in the 3p26.3-p25.3 region, resulting in a heterozygous deletion mutation of the BRPF1 gene; thus, the patient was diagnosed with 3p deletion syndrome. At the time of diagnosis, the child was one year of age and responded to comprehensive rehabilitation training. A total of 25 well-documented cases were found in the literature, of which 17 cases had an onset within one year of age and mainly manifested with mental and motor developmental retardation and peculiar facial features, with different gene deletions depending on the size and location of the 3p deletion. Conclusion: 3p deletion syndrome has a complicated clinical phenotype with varying degrees of severity that can easily result in missed diagnosis and misdiagnosis. Most cases gain some social functioning after rehabilitation. Genetic testing should be conducted for a definitive diagnosis.